2010
DOI: 10.1302/0301-620x.92b3.22579
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vacuum mixing and pre-heating the femoral component on the mechanical properties of the cement mantle

Abstract: We investigated the effect of pre-heating a femoral component on the porosity and strength of bone cement, with or without vacuum mixing used for total hip replacement. Cement mantles were moulded in a manner simulating clinical practice for cemented hip replacement. During polymerisation, the temperature was monitored. Specimens of cement extracted from the mantles underwent bending or fatigue tests, and were examined for porosity. Pre-heating the stem alone significantly increased the mean temperature values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Generated porosity and temperature are reportedly comparable in an experimental femur. Elastic modulus and bending strength of the cement mantle were also similar when a pre‐heated stem was used with either hand or vacuum mixed bone cement. This further supports the use of hand mixing both in our experiment and if the stem is to be pre‐heated in a clinical setting.…”
Section: Discussionsupporting
confidence: 80%
“…Generated porosity and temperature are reportedly comparable in an experimental femur. Elastic modulus and bending strength of the cement mantle were also similar when a pre‐heated stem was used with either hand or vacuum mixed bone cement. This further supports the use of hand mixing both in our experiment and if the stem is to be pre‐heated in a clinical setting.…”
Section: Discussionsupporting
confidence: 80%
“…Some researchers have contested the relevance of porosity reduction, suggesting that the porosity of the mantle is not directly linked to the porosity of the material (14,21). However, it has more recently been shown that reducing porosity leads to improved cement mantle strength (1,22). A number of techniques are available when attempting to measure the porosity within a cement sample.…”
Section: Discussionmentioning
confidence: 99%
“…Pre‐chilling of the metal implant has been shown to reduce maximum temperature, however, pre‐chilling of bone cement prior to mixing has been shown to increase maximum temperature for some cement formulations . Maximum temperature and curing time have been used to quantify the rate of reaction and heat generation within the cement layer . Increases or decreases in curing time can also represent changes in the amount of time the cement can be handled prior to implantation.…”
mentioning
confidence: 99%
“…Handling and insertion, shrinkage of the cement, and evaporation of the monomer can all contribute to porosity within the cement mantle . It has been shown that porosity of bone cement can be reduced at the metal‐cement interface through preheating of the metal implant, however, this technique additionally raises the risk of thermal necrosis. Alternatively, vacuum‐mixing offers a reduction in bulk porosity, which is correlated with increased strength, fracture toughness, and fatigue life in vitro, however, the in vivo clinical benefit is somewhat more controversial and unproven .…”
mentioning
confidence: 99%
See 1 more Smart Citation